Active Learning as an Approach to Fostering EFL Learners’ Speaking Skills and Willingness to Communicate: A Mixed-methods Inquiry - Zeinab Azizi; Ehsan Namaziandost; Parisa Ashkani (Issues in Language Teaching, 2022)
Emerging as a novel instructional approach, Active Learning (AL) is predicated on paving the way for students to actively explore knowledge and reflect on the learning processes. Despite its robust theoretical foundations, AL has rarely been implemented by English as a foreign language (EFL) teachers in the Iranian context. A lion’s share of this hesitation may be ascribed to the lack of strong empirical findings to underscore its advantages and disadvantages. To fill in this lacuna, this mixed-methods study inspected the effects of AL on fostering EFL learners’ speaking skills (SSs) and willingness to communicate (WTC) in the Iranian context. For this purpose, a total of 87 intermediate EFL learners, were selected using a convenience sampling method. They were homogenized through a Key English Test (KET) and randomly assigned to an experimental group (n = 26) and a control group (n = 25). Afterward, a pre-test, interventions (lasting 18 75-miniute sessions held twice a week), and a post-test were administered. Then, eight participants who actively participated in the interventions were invited to a focus group interview to express their perceptions of and experiences with AL. The results of the independent samples t-tests documented that AL substantially contributed to fostering the participants’ SSs and WTC on the post-test. Additionally, the qualitative findings of a thematic coding analysis yielded four overarching themes; facilitating knowledge construction, developing metacognitive awareness, promoting self-regulated learning, and fostering motivation. The findings provide a number of implications for pertinent stakeholders.